2020
DOI: 10.1186/s12864-020-6586-0
|View full text |Cite
|
Sign up to set email alerts
|

Loci associated with variation in gene expression and growth in juvenile salmon are influenced by the presence of a growth hormone transgene

Abstract: Background: Growth regulation is a complex process influenced by genetic and environmental factors. We examined differences between growth hormone (GH) transgenic (T) and non-transgenic (NT) coho salmon to elucidate whether the same loci were involved in controlling body size and gene expression phenotypes, and to assess whether physiological transformations occurring from GH transgenesis were under the influence of alternative pathways. The following genomic techniques were used to explore differences between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 79 publications
(96 reference statements)
0
4
0
Order By: Relevance
“…To some extent, these studies have revealed the relationship between growth performance differences and genes in aquatic animals; however, the available research is insufficient to elucidate the mechanisms of transcriptome-level regulation of growth differences in wild-type bony fishes, especially cichliforms. In a study of non-wild type coho salmon ( Oncorhynchus keta ), McClelland et al (2020) found that comparative transcriptome results between GH transgenic (T) and non-transgenic (NT) individuals with different growth performance (T large , T small , NT large , and NT small ) indicated that there are widespread regulatory influences acting to influence body size and gene expression traits, in addition to the effects of GH transgenesis. Those authors also showed that multiple regulatory loci affecting gene expression were shared between fast-growing and slow-growing fish within T or NT groups, but no such regulatory loci were found to be shared between those two groups ( McClelland et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To some extent, these studies have revealed the relationship between growth performance differences and genes in aquatic animals; however, the available research is insufficient to elucidate the mechanisms of transcriptome-level regulation of growth differences in wild-type bony fishes, especially cichliforms. In a study of non-wild type coho salmon ( Oncorhynchus keta ), McClelland et al (2020) found that comparative transcriptome results between GH transgenic (T) and non-transgenic (NT) individuals with different growth performance (T large , T small , NT large , and NT small ) indicated that there are widespread regulatory influences acting to influence body size and gene expression traits, in addition to the effects of GH transgenesis. Those authors also showed that multiple regulatory loci affecting gene expression were shared between fast-growing and slow-growing fish within T or NT groups, but no such regulatory loci were found to be shared between those two groups ( McClelland et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of non-wild type coho salmon ( Oncorhynchus keta ), McClelland et al (2020) found that comparative transcriptome results between GH transgenic (T) and non-transgenic (NT) individuals with different growth performance (T large , T small , NT large , and NT small ) indicated that there are widespread regulatory influences acting to influence body size and gene expression traits, in addition to the effects of GH transgenesis. Those authors also showed that multiple regulatory loci affecting gene expression were shared between fast-growing and slow-growing fish within T or NT groups, but no such regulatory loci were found to be shared between those two groups ( McClelland et al, 2020 ). This demonstrates the complexity and important research potential of gene expression differences among individuals with different growth performance.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic and endocrinological analyses revealed that, relative to wild-type, GH transgenesis and domestication affected GH and IGF-1 hormone levels as well as gene expression in similar ways (Devlin et al 2009 ; Devlin et al 2013 ; Fleming et al 2002 ; Tymchuk et al 2009 ). Despite parallel responses, genome-wide association studies (GWAS) have found that loci influencing growth and gene expression levels are highly distinct between GH transgenic and wild-type salmon (Kodama et al 2018b ; Mcclelland et al 2020 ). The degree of growth enhancement is also influenced by environmental conditions and genotype-by-environment interactions.…”
Section: Introductionmentioning
confidence: 99%
“…As a model target species, Yasawa et al (2005) evaluated gene transfer methods for black tiger shrimp using green fluorescence protein (GFP) and chloramphenicol acetyl transferase (CAT) as a marker gene. More recently, growth-enhanced transgenic organisms have been the main research subject in many fish species through the introduction of growth hormone gene constructs (Alzaid et al 2018;McClelland et al 2020). However, transgenic technology provides a great prospect in developing strains that have high resistance to disease-causing pathogens.…”
Section: Introductionmentioning
confidence: 99%